Strobilanthes tricostata, a new species of Acanthaceae from the Western Ghats, India - Thomas, Sinjumol; Mani, Bince; Britto, Susai John; Krishna Pillai, Pradeep Annavi Veettil (Phytotaxa, 2019)
Strobilanthes tricostata, a new species with semelparous life history strategy, is described from the Megamalai hills, Tamil Nadu. Pollen morphology, phenology, distribution, conservation status and notes on allied taxa are provided along with illustrations.